IMPROVING STUDENTS' SELF-OPENNESS WITH THE HELP OF WHATSAPP VIDEO CALLS DURING CYBER-COUNSELING-BASED GROUP COUNSELING - Dihra Ardaly Siregar; M. Hafizh Fadilah Siregar; Sufina Dewi; Afwan Syahril Manurung (Yayasan Nuraini Ibrahim Mandiri, 2024)
This study aims to discuss the role of cyber counseling in improving guidance and counseling services, especially among adolescents, by utilizing advances in internet technology. Cyber ​​counseling (eCounseling) is a form of professional counseling service that is carried out through electronic media such as text messages, email, or video calls. Along with the development of technology, counseling services are no longer limited to face-to-face interactions, but can be done virtually, providing flexibility of time and place for clients and counselors. Physical distance is no longer an obstacle in the counseling process, making it more accessible, especially for individuals who cannot or do not want to meet counselors directly. This study examines various models of cyber counseling services, including website-based, email, and video conferencing, and their impact on increasing student self-disclosure. This study shows that cyber counseling can increase students' levels of self-disclosure by providing a safe and comfortable space to express problems without shame or anxiety. Therefore, cyber counseling services are very relevant for adolescents who need emotional support, especially in the context of psychological development that occurs during the transition to adulthood. Keywords: Cyber ​​Counseling, eCounseling, Self-Disclosure, Guidance and Counseling Services, Information Technology, Teenagers, Video Call, WhatsApp